ABOUT THE NEED TO DEVELOP INNOVATIVE DECOMPOSITION METHODOLOGICAL ASPECTS AS A WAY TO INCREASE EFFECTIVENESS IN CREATING HIGH-TECH PRODUCTS - Tsybulevsky , Sergey (Revista Inclusiones, 2020)
This article’s methodological basis is the work of domestic and foreign authors in the Research and Development (R&D) economic results analysis field in the high-tech products development. The proposed methodological approaches, taking into account the practice of implementing the results obtained in the R&D field, are focused primarily on the existing scientific potential rational use and ensuring scientific developments cost reduction. This study’s purpose is to confirm the hypothesis of the interdependence presence in achieving potentially high results when performing R&D, provided that the previously obtained results of scientific and technical activity are decomposed. This article examines the issue’s current state of the methodological approaches topics development in the R&D results analysis field in the high-tech products development, as an integral part of the management system tool in the innovative development field and the subsequent formation of a new technological economic paradigm. The methodological aspects of the innovative decomposition and subsequent analysis in the R&D field are based on the need for a comprehensive and critical assessment of the obtained results’ economic effect based on retrospective and prospective studies, the results of which will subsequently form the basis for evaluating the program planning documents effectiveness and rational resources allocation.